2013
DOI: 10.1111/spc3.12049
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment and Advocacy for Domestic Violence Victims

Abstract: Empowering women victims of domestic violence has been a goal of advocacy since its inception. The concept of empowerment is also widely shared in social science disciplines where the goal of applied research is to address the lived effects of social injustice. While in some fields, such as community psychology, there has been a long history of engaging theoretically with the concept of empowerment, elsewhere theory has received less attention. In the case of addressing domestic violence, victim advocacy has o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…Despite a desire to empower women who are leaving their abusive relationships, many existing services do not adequately address their unique circumstance (Goodman et al, 2016; Kasturirangan, 2008; Morgan & Coombes, 2013; Wood, 2015). Instead of attempting to empower women through a reliance on others, it is crucial for survivors to navigate empowerment processes on their own (Morgan & Coombes, 2013), which is in alignment with a feminist perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a desire to empower women who are leaving their abusive relationships, many existing services do not adequately address their unique circumstance (Goodman et al, 2016; Kasturirangan, 2008; Morgan & Coombes, 2013; Wood, 2015). Instead of attempting to empower women through a reliance on others, it is crucial for survivors to navigate empowerment processes on their own (Morgan & Coombes, 2013), which is in alignment with a feminist perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has assessed the impact of access to microfinance services on different components of women’s beliefs about their personal strength. Specifically, it has examined self-esteem (e.g., Stromquist, 1995 ; Basargekar, 2009 ; Kato and Kratzer, 2013 ), control beliefs (e.g., Morgan and Coombes, 2013 ; Hansen, 2015 ), self-confidence ( Burra et al, 2005 ; Kim et al, 2007 ), and self-efficacy (e.g., Kato and Kratzer, 2013 ). We refer to these components as personal empowerment as they assess different psychological aspects about personal beliefs and actions.…”
Section: Women’s Empowerment In the Context Of Microfinance Servicesmentioning
confidence: 99%
“…Further research in this field showed that women reported higher levels of self-esteem (e.g., Stromquist, 1995 ; Basargekar, 2009 ; Kato and Kratzer, 2013 ), stronger internal control beliefs (e.g., Morgan and Coombes, 2013 ; Hansen, 2015 ), and increased self-confidence ( Burra et al, 2005 ; Kim et al, 2007 ). Overall, research investigating the impact of microfinance services showed mostly positive impacts for personal empowerment with respect to individual choice.…”
Section: Women’s Empowerment In the Context Of Microfinance Servicesmentioning
confidence: 99%
“…5052 This may be especially true for justice involved women who are returning to communities that provide few supports to meet their needs. Knowledge of resources and having a way to obtain resources may be components of the empowerment process.…”
Section: Introductionmentioning
confidence: 99%